An algebra problem by Rocco Dalto

Algebra Level pending

Let P 2 \mathbb P_{2} denote the set of all polynomials of degree two and R 3 \mathbb R^3 denote the set of all vectors in three space.

Let f : P 2 R 3 f: \mathbb P_{2} \rightarrow \mathbb R^3 be linear transform defined by

f ( p 0 + p 1 x + p 2 x 2 ) = ( p 0 + p 1 p 1 + p 2 p 0 + p 2 ) f(p_{0} + p_{1} x + p_{2} x^2) = \left( \begin{array}{ccc} p_{0} + p_{1} \\ p_{1} + p_{2} \\ p_{0} + p_{2} \\ \end{array} \right)

Let
A = { 1 + x , x + x 2 , x 2 } A = \{1 + x, x + x^2, x^2 \} be a basis for P 2 \mathbb P_{2} and
B = { ( 1 1 1 ) , ( 1 1 1 ) , ( 1 0 1 ) } B = \left \{ \left( \begin{array}{ccc} 1 \\ -1 \\ 1 \\ \end{array} \right), \left( \begin{array}{ccc} -1 \\ 1 \\ 1 \ \end{array} \right), \left( \begin{array}{ccc} 1 \\ 0 \\ 1 \ \end{array} \right) \right \} be a basis for R 3 . \mathbb R^3. .

Let the matrix M = [ a i j ] 3 x 3 M = [a_{ij}]_{3 \: x \: 3} represent the linear transform above.

If [ p ] A = ( x 1 x 2 x 3 ) [p]_{A} = \left( \begin{array}{ccc} x_{1} \\ x_{2} \\ x_{3} \ \end{array} \right) , [ f ( p ) ] B = ( 1 2 3 ) \: [f(p)]_{B} = \left( \begin{array}{ccc} 1 \\ 2 \\ 3 \ \end{array} \right) , S = j = 1 3 x j \: S = \sum_{j = 1}^{3} x_{j} , p = b 0 + b 1 x + b 2 x 2 \: p = b_{0} + b_{1} x + b_{2} x^2 , and T = j = 0 2 b j \: T = \sum_{j = 0}^{2} b_{j} ,

Find: S + T S + T .

Refer to previous problem. . .


The answer is 10.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Dec 29, 2016

f ( 1 + x ) = ( 2 1 1 ) = α 1 ( 1 1 1 ) + α 2 ( 1 1 1 ) + α 3 ( 1 0 1 ) = ( α 1 α 2 + α 3 α 1 + α 2 α 1 + α 2 + α 3 ) f(1 + x) = \left( \begin{array}{ccc} 2 \\ 1 \\ 1 \\ \end{array} \right) = \alpha_{1} \left( \begin{array}{ccc} 1 \\ -1 \\ 1 \\ \end{array} \right) + \alpha_{2} \left( \begin{array}{ccc} -1 \\ 1 \\ 1 \\ \end{array} \right) + \alpha_{3} \left( \begin{array}{ccc} 1 \\ 0 \\ 1 \\ \end{array} \right) = \left( \begin{array}{ccc} \alpha_{1} - \alpha_{2} + \alpha_{3} \\ -\alpha_{1} + \alpha_{2} \\ \alpha_{1} + \alpha_{2} + \alpha_{3} \\ \end{array} \right)

f ( x + x 2 ) = ( 1 2 1 ) = ( β 1 β 2 + β 3 β 1 + β 2 β 1 + β 2 + β 3 ) f(x + x^2) = \left( \begin{array}{ccc} 1 \\ 2 \\ 1 \\ \end{array} \right) = \left( \begin{array}{ccc} \beta_{1} - \beta_{2} + \beta_{3} \\ -\beta_{1} + \beta_{2} \\ \beta_{1} + \beta_{2} + \beta_{3} \\ \end{array} \right)

f ( x 2 ) = ( 0 1 1 ) = ( γ 1 γ 2 + γ 3 γ 1 + γ 2 γ 1 + γ 2 + γ 3 ) f(x^2) = \left( \begin{array}{ccc} 0 \\ 1 \\ 1 \\ \end{array} \right) = \left( \begin{array}{ccc} \gamma_{1} - \gamma_{2} + \gamma_{3} \\ -\gamma_{1} + \gamma_{2} \\ \gamma_{1} + \gamma_{2} + \gamma_{3} \\ \end{array} \right)

Solving the system:

α 1 α 2 + α 3 = a \alpha_{1}^{*} - \alpha_{2}^{*} + \alpha_{3}^{*} = a α 1 + α 2 = b -\alpha_{1}^{*} + \alpha_{2}^{*} = b α 1 + α 2 + α 3 = c \alpha_{1}^{*} + \alpha_{2}^{*} + \alpha_{3}^{*} = c

( α 1 α 2 α 3 ) = ( c a 2 b 2 c a 2 a + b ) \implies \left( \begin{array}{ccc} \alpha_{1}^{*} \\ \alpha_{2}^{*} \\ \alpha_{3}^{*} \\ \end{array} \right) = \left( \begin{array}{ccc} \dfrac{c - a - 2b}{2} \\ \dfrac{c - a}{2} \\ a + b \\ \end{array} \right) \implies

( α 1 α 2 α 3 ) = ( 3 2 1 2 3 ) , ( β 1 β 2 β 3 ) = ( 2 0 3 ) , ( γ 1 γ 2 γ 3 ) = ( 1 2 1 2 1 ) \left( \begin{array}{ccc} \alpha_{1} \\ \alpha_{2} \\ \alpha_{3} \\ \end{array} \right) = \left( \begin{array}{ccc} -\dfrac{3}{2} \\ -\dfrac{1}{2} \\ 3 \\ \end{array} \right), \: \left( \begin{array}{ccc} \beta_{1} \\ \beta_{2} \\ \beta_{3} \\ \end{array} \right) = \left( \begin{array}{ccc} -2 \\ 0 \\ 3 \\ \end{array} \right), \: \left( \begin{array}{ccc} \gamma_{1} \\ \gamma_{2} \\ \gamma_{3} \\ \end{array} \right) = \left( \begin{array}{ccc} -\dfrac{1}{2} \\ \dfrac{1}{2} \\ 1 \\ \end{array} \right) \implies

Matrix M = 3 2 2 1 2 1 2 0 1 2 3 3 1 M = \left| \begin{array}{ccc} -\dfrac{3}{2} & -2 & -\dfrac{1}{2} \\ -\dfrac{1}{2} & 0 & \dfrac{1}{2} \\ 3 & 3 & 1 \\ \ \end{array} \right|

d e t ( M ) = 1 < > 0 det(M) = -1 <> 0 \implies [ f ( p ) ] B = ( 1 2 3 ) = 3 2 2 1 2 1 2 0 1 2 3 3 1 ( x 1 x 2 x 3 ) \: [f(p)]_{B} = \left( \begin{array}{ccc} 1 \\ 2 \\ 3 \ \end{array} \right) = \left| \begin{array}{ccc} -\dfrac{3}{2} & -2 & -\dfrac{1}{2} \\ -\dfrac{1}{2} & 0 & \dfrac{1}{2} \\ 3 & 3 & 1 \\ \ \end{array} \right| \left( \begin{array}{ccc} x_{1} \\ x_{2} \\ x_{3} \ \end{array} \right) has a unique solution.

Rewriting the system M [ p ] A = [ f ( p ) ] B M [p]_{A} = [f(p)]_{B} \implies 3 x 1 + 4 x 2 + x 3 = 2 3 x_{1} + 4 x_{2} + x_{3} = -2 x 1 + x 3 = 4 -x_{1} + x_{3} = 4 3 x 1 + 3 x 2 + x 3 = 3 3 x_{1} + 3 x_{2} + x_{3} = 3

x 3 = 4 + x 1 x 2 = 5 , x 1 = 7 2 x 3 = 15 2 \implies x_{3} = 4 + x_{1} \implies x_{2} = -5, \: x_{1} = \dfrac{7}{2} \implies x_{3} = \dfrac{15}{2}

[ p ] A = ( 7 2 5 15 2 ) S = j = 1 3 x j = 6 \implies \: [p]_{A} = \left( \begin{array}{ccc} \dfrac{7}{2} \\ -5 \\ \dfrac{15}{2} \ \end{array} \right) \implies S = \sum_{j = 1}^{3} x_{j} = \boxed{6} ,

a n d [ p ] A = ( 7 2 5 15 2 ) and \: [p]_{A} = \left( \begin{array}{ccc} \dfrac{7}{2} \\ -5 \\ \dfrac{15}{2} \ \end{array} \right) \implies

p = 7 5 ( 1 + x ) + 5 ( x + x 2 ) + 15 2 x 2 = 7 2 3 2 x + 5 2 x 2 T = j = 0 2 b j = 9 2 p = \dfrac{7}{5} (1 + x) + -5 (x + x^2) + \dfrac{15}{2} x^2 = \dfrac{7}{2} - \dfrac{3}{2} x + \dfrac{5}{2} x^2 \implies T = \sum_{j = 0}^{2} b_{j} = \boxed{\dfrac{9}{2}}

S + T = 21 2 \therefore \: S + T = \boxed{\dfrac{21}{2}} or 10.5 \boxed{10.5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...